The Influence of Organizational Citizenship Behavior, Organizational Commitment, and Organizational Culture on Production Employee Performance with Job Satisfaction as an Intervening Variable: (Case Study at PT. Casuarina Harnessindo Pemalang) - Rengga Kusuma Putra; Tri Handayani; Ulil Inayah (Digital Innovation : International Journal of Management, 2024)
This research is entitled "The Influence of Organizational Citizenship Behavior, Organizational Commitment and Organizational Culture on the Performance of Production Employees with Job Satisfaction as an Intervening Variable (Case Study at PT. Casuarina Harnessido Pemalang)". The purpose of this study was to determine the effect of Organizational Citizenship Behavior, organizational commitment and Organizational Culture on the Performance of Production Employees with Job Satisfaction as an Intervening Variable. In this research using purposive sampling technique with a total sample of 90 respondents. The testing in this research was carried out by testing validity, reliability testing, classical assumption test, multiple linear regression analysis, hypothesis testing in the form of t test, F test, R2 test, path analysis and Sobel test. In this research, there is a partially significant positive effect between the OCB variable on the performance of production employees with a value of tcount > ttable (2.184>1.662), organizational commitment to the performance of production employees with a value of tcount> ttable (3.689>1.662), organizational culture on the performance of production employees. with a value of tcount > ttable (3.160>1.662), job satisfaction affects the performance of production employees with a value of tcount > ttable (2,606>1,662). From the Sobel test results show that job satisfaction mediates the effect of OCB on the performance of production employees with a value of tcount > ttable (3.0496>1.6619), job satisfaction mediates the effect of organizational commitment on employee performance. production with a value of tcount > ttable (1.7531>1.6619), job satisfaction mediates the effect of organizational culture on the performance of production employees with a value of tcount > ttable (1.9392>1.6619).